PEMANFAATAN UDARA BUANG EXHAUST FAN UNTUK PEMBANGKIT LISTRIK TENAGA BAYU DENGAN PENGARUH PENAMBAHAN HONEYCOMB BERBASIS ATMEGA 2560 - Yoga Kusuma Wardhana; Cok Gede Indra Partha; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2021)
Energy needs are increasing from year to year in line with the increasing population,economic growth, and high energy consumption. More than 86% of the world's energy todaycomes from fossil fuels, while the world's energy demand is increasing. One of theconsiderations for overcoming pollution caused by fossil fuels is to seek alternative energysystems. More than 90% of the energy that affects greenhouse gas emissions is the result ofburning fuels globally. Exhaust Fan is a good system for wind power extraction. This air exhaustsystem is suitable for power plants with wind turbines as a drive where the resulting wind speedis higher and consistent when compared to natural wind, but has turbulent characteristics. Thiswind is not good for the wind turbine. A honeycomb is a tool used to reduce this turbulentcharacteristic. The results obtained by the addition of a hexa type Honeycomb to the exhaustfan with a speed of 6m/s using a savonius type turbine, there was a decrease in turbine speedwhich was previously unstable between 952 to 1007 rpm to 866 rpm and the generator outputpower decreased by 0.3 watts. The addition of Honeycomb makes the turbine rotate speedstable at 866 rpm and the wind flow becomes laminar.